PENGEMBANGAN MODUL FISIKA DENGAN MODEL KREATIF DAN PRODUKTIF - Muhammad Ali; Andi Karlina (STKIP Paris Barantai, 2018)
AbstractThis research aims to produce physics modules with creative and productive learning models on subjects Temperature, Heat, and Heat Transfer Â that meet the criteria worthy. And to know the student's learning achievement by using physics module with creative and productive learning model on material of Temperature, Calor, and Heat Transfer. The method used in this research is the method of research and development with quantitative descriptive that is to describe objectively using numbers in making the module by knowing the feasibility of a module and knowing student achievement. This type of research is a development research conducted by teachers to create teaching materials. Type of research and development with quantitative and quantitative data analysis through the steps of defining, planning, developing and disseminating and presenting data with technique, posttest-pretest, questionnaire, validity sheet and module. The results showed that the development of physics module with creative and productive learning model on Temperature, Heat, and Heat Transfer materials met the criteria very feasible with the eligibility criteria of 81.84% module. Based on the hypothesis test, the value of 0.421> 0,05 was found to be rejected. So it is concluded that there is no difference in learning achievement. However, if seen from the average student before the test and after the test then there is an average difference of pretest of 40.33 to a posttest of 46.40. Â Key word: Physics module, creative and productive learning models, 4D depelopment